Relationship ofselected psychological variables on playing ability between Kerala departmental Volleyball Players - Mr. Jijith , Dr. S. Dhanaraj , Dr. Babu.P (Cuestiones de Fisioterapia, 2024)
The purpose of the study was to examine the relationship between selectedpsychological variables and volleyball playing ability of department volleyball players. Forwhich thirty volleyball players were selected from Department of Physical Education,Calicut University, Kerala. The selected player’s age was ranged from 18-28 years. Theselected psychological variables were aggression, self-confidence, stress and it wasmeasured by standardized questionnaire.